Perfect Competition, Average Cost Pricing and the Price Equation - Laden, Ben E. (The Review of Economics and Statistics, 1972)
EMPIRICAL studies of aggregate price equations have shed little light on the choice among alternative theories of price-setting behavior. Specification of the price equation generally makes appeal to both profit maximizing and average cost pricing assumptions.1 Yet little effort has been spent in testing the comparative explanatory power of these alternatives.2 The choice among theories has important implications. The expected pattern of pricewage interactions, questions of bias and identification of the price equation, and use of the price equation for forecasting should all be analyzed with respect to particular hypotheses concerning pricing behavior.3 The need is for more explicit formulation of models and testing of hypotheses. A test of the relative explanatory power of a perfectly competitive model and a general version of average cost pricing is reported in this paper. Two supply and demand models of the final output of the manufacturing sector are specified. These show important differences in the relationship between the price level and its determinants. An empirical test for the United States manufacturing sector is provided.